IFMBE Proceedings : 12th International Conference On Biomedical Engineering (ICBME 2005) 7 - 10 December 2005, Singapore
The International Federation for Medical and Biological Engineering, IFMBE, is a federation of national and transnational organizations which represent national interests in medical and biological engineering. The objectives of the IFMBE are scientific, technological, literary, and educational. Within the field of medical, clinical, and biological engineering, IFMBE's aims are to encourage research and the application of knowledge, and to disseminate information and promote collaboration.